Mati Syahid Dalam Perspektif Iman Kristen Ditinjau dari Kitab 2 Timotius 2:1-13 - Tina, Jumreni (Pusat Studi Pentakosta Indonesia, 2023)
Martyrdom is an event experienced by people because they defend the teachings they believe in. Martyrdom from a Christian perspective, a review of the book of 2 Timothy 2:1-13, is an effort made to answer various paradigms that emerge in society, the nation, especially the Church. . The purpose of writing is to explain how the book of Philippians views martyrdom from the perspective of the Christian faith, which then becomes a guide for Christians so that they do not misinterpret the meaning of “Shaheed Death”. In this writing, we use a qualitative research method with a literature review method to explore and find out the purpose and meaning of martyrdom and its relationship to 2 Timothy 2:1-13. The meaning of “martyrdom” in this context refers to the great sacrifice a person can make, even to the point of death, for the sake of faith and service to God. In the context of Christian life, Martyrdom refers to someone who dies because of their faith. This reflects a willingness to sacrifice one’s life for the sake of truth and faith in Christ.AbstrakMati syahid merupakan suatu peristiwa yang dialami orang-orang karena membela ajaran yang diyakini, mati syahid dalam perspektif Kristen ditinjau dari kitab 2 Timotius 2:1-13 merupakan sebuah usaha yang dilakukan untuk menjawab berbagai paradigma yang muncul ditengah masyarakat, Bangsa, secara khusus Gereja. Tujuan dari penulisan untuk menjelaskan bagaimana kitab filipi memandang mati syahid dalam perspektif iman Kristen yang kemudian menjadi pegangan bagi umat Kristen sehingga tidak salah dalam menafsirkan arti “Mati Syahis”. Dalam penulisan ini menggunakan metode penelitian kualitatif dengan metode kajian pustaka untuk menggali serta mencari tahu maksud, makna dari mati syahid dan kaitannya dengan 2 Timotius 2:1-13. Makna “mati syahid” dalam konteks ini merujuk pada pengorbanan yang besar yang seseorang bisa berikan, bahkan sampai pada kematian, demi iman dan pelayanan kepada Tuhan. Dalam konteks kehidupan Kristen, mati syahid mengacu pada seseorang yang meninggal karena imannya. Hal ini mencerminkan kesediaan untuk mengorbankan nyawa demi kebenaran dan iman dalam Kristus.